Pemanfaatan Media Permainan Papan Geometri Untuk Pengembangan Kognitif Anak Usia 3-5 Tahun - Octaviani, Rosa; RR. Deni Widjayatri (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2023)
Abstract: Utilization Of Geometry Board Game Media For Cognitive Development Of Children Aged 3-5 Years. Learning while playing is the most preferred learning method by children. The geometry board is an educational game that stimulates various aspects of early childhood development, especially the cognitive aspect. The purpose of this study was to determine the effectiveness and benefits of geometry board games in Gunungsari Village with various different stages of development for each child. The method used is a descriptive qualitative method using data sources from 5 children aged 3-5 years. Data collection using interview and observation techniques. As a result of these geometry board games, children can become more familiar with different geometric shapes, develop problem-solving, creativity, and logical thinking skills, and strengthen their understanding of colors and shapes. In addition, this game also creates a fun learning atmosphere so that it can increase concentration, also involve children in social interaction. In conclusion, this geometry board game can be used in the development of cognitive development aspects of children aged 3-5 years. Keywords: Board Geometry Game, Cognitive Development